Efficacy of Different Glyphosate rates of Application on Weed Infestation in Citrus Orchards - B, Hajjaj; A, El Oualkadi (International Journal of Environment, Agriculture and Biotechnology, 2019)
Citrus weeding trial was conducted during the 2019 growing season. The aimof this study is to investigate the effect of three glyphosate rates of application on weed infestation in citrus orchards. Dominant weed botanical families belong to: Asteraceae, Amaranthaceae, Caryophyllaceae,Solanaceae, Poaceae and Primulaceae.Results showed that glyphosate applied at 1080 g/hectareand 720 g/hectare provided good weed control. Glyphosate rates of application at 1080 g/hectare and 720 g/hectare recorded respectively 88.07% and 81% of weed density reduction compared to weed density in the control plots and 93.36% and 77.41% of weed dry biomass reduction compared to weed dry biomass in the control plots.Glyphosate rates of application at 1080 g/hectarerecorded 95% of visual weed control notation compared to weed infestation in the control plots.Glyphosate applied at 360 g/hectare showed very low efficacy and is not recommended in chemical weed control program in citrus orchards.